Advancement in Sustainable 3D Concrete Printing: A Review on Materials, Challenges, and Current Progress in Australia - Kumari Gamage; Sabrina Fawzia; Tatheer Zahra; Muge Belek Fialho Teixeira; Nor Hafizah Ramli Sulong (Buildings, 2024)
Three-dimensional concrete printing (3DCP) is a sustainable and green approach for rapid construction with the ability to create complex shapes to preserve the intended aesthetic appearance for an affordable cost. Even after a decade of attempts, there are many limitations and challenges to applying this technology for constructions without borders. The lack of guidelines for mix designs, quality control procedures during extrusion, printing and building phases, compatibility of material with extruder, standard testing, and guidelines to verify suitability of mixture with respect to the application and exposure conditions and limited machine capacity are several areas to be addressed for applications without borders. The development of 3DCP applications as a sustainable and green technology is another challenging task due to high Portland cement consumption in 3DCP. However, reducing the high usage of ordinary Portland cement (OPC) with pozzolanic waste materials replacement and environmentally friendly cement indicates the direction of moving 3DCP into a sustainable pathway. The authors reviewed more than 200 refereed articles published on materials and techniques in 3DCP. Inconsistency in disseminating knowledge in research articles has hindered the creation of a monolithically connected chain of research efforts and findings in accelerating the development and adoption of this technology. This paper summarizes the common approach to developing 3DCP mix designs and identifies the key areas for the future development of materials and techniques and challenges to be addressed for the global adoption of 3DCP. The current progress and challenges in the context of Australia’s construction industry and future trends for the acceptance of 3DCP are also reviewed.